Collaborative Strategy of Schools and Parents in Strengthening Character Education for Students - Tri Wahyuningtyas Gamayanti; Saryanto Saryanto; Rahmat Mulyono (CV. Edujavare Publishing, 2026)
In the era of globalization and rapid technological advancement, children are increasingly exposed to various social influences that may affect their attitudes and character development. This study aims to analyze the collaborative strategies implemented by SD Negeri 1 Kwadungan Jurang and parents in strengthening students’ character education, as well as to identify the supporting and inhibiting factors affecting their implementation. The study employed a qualitative case study approach involving the principal, teachers, parents, and students as research participants. Data were collected through semi-structured interviews, observations, and document analysis, and were analyzed using data reduction, data display, and conclusion drawing techniques. The findings reveal that collaborative strategies are implemented through continuous communication, parental involvement in school programs, collaborative monitoring of students’ behavior, role modeling by teachers and parents, and the integration of religious and cultural values into daily educational practices. These strategies contribute to the development of positive character traits, including discipline, honesty, responsibility, respect, and cooperation among students. The study also found that the implementation of collaboration is supported by strong commitment from stakeholders, effective communication, a positive school climate, and shared moral values. However, several challenges were identified, including limited parental availability, differences in parenting approaches, technological influences, and resource constraints. The study concludes that effective collaboration between schools and parents is essential for strengthening character education and creating a consistent learning environment that supports students’ moral and social development.